Faktor Pengaruh Penerapan Keselamatan dan Kesehatan Kerja (K3) pada Proyek Pembangunan Struktur Gedung XYZ di Kota Surabaya - Mubin, Muhammad Fadhul; Beatrix, Michella; Firmansyah, Mochamad (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
High-rise building construction projects have a high risk of occupational accidents, particularly for field workers. Therefore, the implementation of a well-planned Occupational Safety and Health (OSH) Management System supported by adequate safety facilities is essential. This study aims to analyze the implementation of OSH in the construction project of the XYZ building structure in Surabaya and to identify the dominant influencing factors. The method used is a quantitative approach through questionnaires, with respondents consisting of project staff from contractors and supervising consultants. Data analysis includes validity testing, reliability testing, normality testing, F-test (simultaneous), and T-test (partial). The results show that the factors influencing OSH implementation consist of OSH knowledge (8.97%), OSH management (52.99%), OSH attitudes and behavior (10%), and working conditions and environment (28.04%). The most dominant factor is OSH management, with a percentage of 52.99%.